The effect of four of Richard Mayer's design principles on vocabulary retention in an Afrikaans computer programme. Issue 1 (2nd January 2019) - Beukes, Vernita
Abstract: The research discussed in this article is specifically aimed at non-Afrikaans-speaking international students served by the Language Centre at Stellenbosch University. As a result of students who would like to become proficient in Afrikaans during their stay in South Africa, many of them choose the course Beginner Afrikaans Vlak 1 (Beginner Afrikaans Level 1). The course focuses primarily on communicative and discourse competence. Students mentioned in the formal evaluation of the course as well as in a needs analysis that they would like to have a chance to revise the course material by accessing a computer programme. The lecturer of the course therefore decided to design a computer programme for the abovementioned course that could be used as a revision tool. Four of the design principles of Mayer (2009) were used to design the computer programme. The aim of the research discussed further in this article is to indicate how the vocabulary retention of students enrolled for the course was affected by these four design principles.